Identification of Invasive Aliens Plant Species in Cultivated Area of Kamojang Crater at Ibun District, Bandung Regency, West Java - Rasiska, Siska; Asdak, Chay; Parikesit, Parikesit; Sudarjat, Sudarjat; Gunawan, Budhi; Setiawan, Iwan; Setiawan, Ditriz (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2023)
The Cultivated Area in Kamojang Crater, Ibun District, Bandung Regency is part of a single landscape mountain, adjacent to conservated and protected areas which has high biodiversity. This study aims to identify invasive alien plants species in cultivated areas, adjacent to conservation and protected areas. The method used is a descriptive qualitative study with the sampling line transect in 500 meter radius of four location, namely near Nature Reserves (NR), near Nature Tourism Parks (NTP), agriculture (A) and near Protected Forests (PF), and this study has done up at July until November, 2022. The results showed that in the cultivated area in Kamojang Crater, Ibun District, Bandung Regency found 41 families and 96 species of understorey, with the highest number being from the Asteraceae, Poaceae and Fabaceae. Diversity of understorey was categorized as high (H'=3.428), evenly distributed (E=0.738), high species richness (R=13.503) and no dominant species (C=0.165). Several understorey, namely 8 orders, 10 families, and 29 species were categorized as invasive aliens plant species, with the highest important values index being Ageratina riparia (99,642%), Imperata cylindrica (72,919%), Paspalum notatum (31,155%), Chromolaena odonata (31,074%), Etlingera elatior (27,905%), Ageratum conyzoides (20,179%), Lantana camara (19,029%), Amaranthus hybridus (18,818%), Pennisetum purpureum (15,120%), Mimosa pudica (15,031%), Crassocephalum crepidioides (14,037%), and Axonopus compresus (10,671%).